The Application of PBL, PJBL, and Inquiry Learning Models on Student Learning Outcomes - Yuni Purnama Sari; Anis Fahrurozi; Isti Khomah; Nia Rosita; Unung Lisnawati; Bambang Samsul Arifin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to examine the effectiveness of Problem-Based Learning (PBL), Project-Based Learning (PJBL), and Inquiry Learning (IL) models on students' cognitive learning outcomes in the Islamic Religious Education and Character subject. The research employed a quantitative approach with a quasi-experimental design and involved three Grade IX classes at Junior High School Madani Boarding School Celak, selected using purposive sampling. A cognitive learning test was used as the research instrument. Since the data were not normally distributed, the analysis was conducted using the non-parametric Kruskal-Wallis test. The results showed no significant difference in students’ cognitive learning outcomes among the PBL, PJBL, and IL groups, with a significance value of 0.920 (p > 0.05). Thus, the three learning models demonstrated relatively equal effectiveness in improving students' cognitive achievement. This study recommends optimizing the implementation of each model through innovative strategies and learning media to further enhance learning outcomes.